Preparation and characterization of sulfonated poly(arylene thioether sulfone)/imino-containing phosphorylated silica particle composite proton exchange membranes. (September 2019) - Hou, Jinghe; Liu, Shanshan; Sun, Xiang; Xiao, Zhenyu; Ding, Huili
In this article, novel nanocomposite proton exchange membranes (PEMs) were prepared by embedding imino-containing phosphorylated silica nanoparticles into a sulfonated poly(arylene thioether sulfone) (SPTES) polymer matrix. SPTES was synthesized via condensation polymerization of 4, 4′-thiobisbenzenethiol, 4, 4′-difluorodiphenylsulfone, and disodium 3, 3′-disulfonate-4, 4′-difluorodiphenylsulfone. The imino-containing phosphorylated silica particles (Si-imP) were prepared by the Kabachnik–Fields reaction, which is confirmed by scanning electron microscopy, Fourier-transform infrared spectroscopy, and energy dispersive spectroscopy. The results showed that the Si-imP were uniformly distributed in the composite membrane. The properties of the composite membranes, including thermal stability, water uptake, swelling ratio, oxidative stability, and proton conductivity, were thoroughly evaluated. Experimental results indicated that Si-imP may be effective reinforcement materials for SPTES membranes. It is noteworthy that an increase in proton conductivity from 0.138 S cm −1 of the SPTES control membrane to 0.173 S cm −1 of the composite membrane was achieved at the Si-imP content of 5 wt% under fully hydrated conditions at 80°C. This finding primarily stems from the fact that the Si-imP could be linked with the sulfonate ion clusters of SPTES to form more continuous ionic networks. These networks act as efficient proton-hopping pathways to enhanced proton conductivity. The nanocomposite membranes are demonstrated to be promising candidates as new polymeric electrolyte materials for PEM fuel cells operated at medium temperatures.